Practical guidance for prescribing trazodone extended-release in major depression. (11th February 2016) - Goracci, Arianna; Forgione, Rocco N; De Giorgi, Riccardo; Coluccia, Anna; Cuomo, Alessandro; Fagiolini, Andrea
Abstract: Introduction : Treatment of major depressive disorder aims for symptom remission and recovery of function, and involves a multifaceted approach including drug therapy, evidence-based psychotherapy, and electroconvulsive therapy, according to disease severity. Antidepressant monotherapy is generally the first-line approach for moderate to severe major depressive disorder (with or without psychotherapy). In some severe cases, patients may require the addition of antipsychotic therapy, electroconvulsive therapy, or antidepressant combination therapy. Areas covered : This article examines the use of trazodone in major depressive disorder, with a focus on practical guidance regarding the use of trazodone extended-release (Contramid ® ). Expert opinion : The extended-release once-a-day formulation of trazodone may provide a combination of efficacy and improved tolerability over other antidepressants and over the conventional immediate-release formulation.